Quantification of Basin-Floor Fan Pinchouts: Examples From the Karoo Basin, South Africa - Hansen, Larissa Anne S.; Hodgson, David Mark; Pontén, Anna; Bell, Daniel; Flint, Stephen (Frontiers in Earth Science, 2019)
The topography of the seabed (orientation and gradient) and rheology of the flows greatly influences the character of basin-floor turbidity current deposits. Therefore, submarine fan pinchouts can help to constrain seabed topography and flow behavior at the time of deposition. Although the depositional architecture of submarine lobe pinchouts has been documented in various basin-fills, the quantification of the rates of change at pinchouts in different paleogeographic positions and basin configurations has not been attempted previously. Here, we utilize extensive outcrops and research boreholes from the oblique up-dip pinchout of Fans 3 and 4 and the lateral pinchout of Fan 3 in the Tanqua depocenter, Karoo Basin, South Africa, to compare sedimentary facies and to quantify the rates of change in gross interval thickness. At the oblique up-dip pinchout, Fan 3 thins abruptly at a rate of 12 m/km, while Fan 4 thins at a rate of 4 m/km. Marked differences between Fans 3 and 4 in sedimentary facies and architecture toward the up-dip pinchout, with termination of lobes in Fan 3 and a channel-lobe transition zone and external levee in Fan 4, suggests progradation of the system. The thinning rate of the lateral pinchout of Fan 3 is 2 m/km, with the presence of hybrid beds in the lower part of Fan 3, while the upper part is dominated by structured sandstones and thin-bedded heterolithics. The variations in facies suggest that lobe-scale frontal and lateral pinchouts are stacked at the lobe complex-scale lateral pinchout of Fan 3, highlighting the importance of a hierarchical understanding when studying basin-floor fan pinchouts. The quantified rates of change in fan thickness and sedimentology on the oblique up-dip and lateral fan pinchouts are markedly different. Contrasting pinchout architecture above slopes with subtle differences in gradient and orientation cautions against the simple definition of reservoir input parameters for stratigraphic traps in submarine fan systems.